Perception of pixelated images - Bachmann, Talis (Academic Press, 2016)
Perception of Pixelated Images covers the increasing use of these images in everyday life as communication, socialization, and commerce increasingly rely on technology. The literature in this book is dispersed across a wide group of disciplines, from perception and psychology to neuroscience, computer science, engineering, and consumer science. The book summarizes the research to date, answering such questions as, What are the spatial and temporal limits of perceptual discrimination of pixelated images?, What are the optimal conditions for maximizing information extracted from pixelated images?, and How does the method of pixelation compromise or assist perception?